2012
DOI: 10.1111/j.1753-4887.2012.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition in the intensive care unit

Abstract: Patients in the intensive care unit (ICU) are unable to nourish themselves orally. In addition, critical illness increases nutrient requirements as well as alters metabolism. Typically, ICU patients rapidly become malnourished unless they are provided with involuntary feeding either through a tube inserted into the GI tract, called enteral nutrition (EN), or directly into the bloodstream, called parenteral nutrition (PN). Between the 1960s and the 1980s, PN was the modality of choice and the premise was that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 60 publications
0
28
0
11
Order By: Relevance
“…However, PN is associated with significant complications such as intestinal failure-associated liver disease (IFALD), sepsis, and metabolic bone disease (MBD) [13]. Several factors have been implicated in the pathogenesis of MBD in the setting of long-term PN administration.…”
Section: Introductionmentioning
confidence: 99%
“…However, PN is associated with significant complications such as intestinal failure-associated liver disease (IFALD), sepsis, and metabolic bone disease (MBD) [13]. Several factors have been implicated in the pathogenesis of MBD in the setting of long-term PN administration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, few participants from KCH reported the rare access to parenteral nutrition including amino acid infusions, which was not reported at QECH. Although some patients with gut failure may benefit from parenteral nutrition, the predominance of enteral nutrition observed in this study is desirable and in line with international trends 6 . Parenteral nutrition is not locally available in Malawi, and the few participants who had had some experience with it used donated supplies; we therefore will not further discuss parenteral nutrition.…”
Section: Discussionmentioning
confidence: 63%
“…Waitzberg et al reported that about half of patients in hospitals in Brazil were malnourished and that physician awareness of malnutrition was low, resulting in under-prescription of nutritional therapy 5 . Enteral nutrition has emerged as the preferred method of nutritional support in critically ill patients as long as the intestines maintain their digestive and absorptive capacity 6 . If the gut cannot be used for some reason, nutritional therapy may be delivered directly into the venous blood (parenteral nutrition) 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sufficiently disabled so that volitional oral feeding is either impossible or unlikely to successfully meet nutrient requirements. [17] Additionally, critically ill patients often have more risks for malnutrition, with high mortality and morbidity rates [8] due to increased metabolic needs and the tendency for underfeeding. [18] These factors can predispose to a systemic inflammatory response, which increases muscle protein catabolism and moderately increases energy expenditure.…”
Section: Discussionmentioning
confidence: 99%